Developing self-aware mindfulness to manage mood disorder in the adolescent - A Case Report - Kiki Puspitasari (ACTA Medical Health Sciences, 2022)
Major depressive disorder (MDD) with psychotic is a complicated affective disease characterized by abnormal clinical sympotms, including neurovegetative disfunction (appetite or sleep disturbances), cognitive dissonance (inappropriate guilt, feelings of worthlessness), aberrant psychomotor activities (agitation or retardation), and elevated suicide risk with psychotic features such as delusions or nihilistic, non-bizarre delusions, somatic, poverty, worthlessness, or delusional beliefs about guilt and being punished, and sometimes appear hallucination. The prevalence of MDD with psychotic features increases with age. In general population, the point prevalence of MDD is about 2% to 4% and it is increasing about 20% lifetime risk. Depression is a leading cause of burden of disease among young people. Current treatments are not uniformly effective, in part due to the heterogeneous nature of MDD. MDDis caused by many factors. A 22-year-old male presented to the inpatient psychiatric unit with suicide attempt. The patient reported experiencing a lack of energy, difficulty falling asleep, lack of motivation, and feeling overwhelmed about his work and experiencing auditoric hallucination. The insight level was 5. Multiaxial diagnosis are axis I: major depressive episode with psychotic symptoms; axis II and III: currently not found; axis IV: problems with workplace; axis V: GAF 20-11. Patient treated with pharmacotherapy group Selective Serotonin Reuptake Inhibitor (SSRI) and second-generation antipsychotics which combined with supportive psychotherapy such as mindfullness. DOI : 10.35990/amhs.v1n1.p45-53 REFERENCES Brown, K. W., & Ryan, R. M. (2004). Perils and promise in defining and measuring mindfulness: Observations from experience. Clinical Psychology: Science and Practice, 11, 242–248. Ohayon, M. M., & Schatzberg, A. F. (2002). Prevalence of depressive episodes with psychotic features in the general population. American Journal of Psychiatry, 159(11), 1855–1861. Fava, M., & Kenneth, K. S. (2000). Major depressive disorder. Neuron, 28(2), 335–351. Chesney, E., Goodwin, G. M., & Fazel, S. (2014). Risks of all-cause and suicide mortality in mental disorders: A meta-review. World Psychiatry, 13(2), 153–160. Kessing, L. V. (2006). Differences in diagnostic subtypes among patients with late and early onset of a single depressive episode. International Journal of Geriatric Psychiatry, 21(12), 1127–1131. Serretti, A., Lattuada, E., Cusin, C., Gasperini, M., & Smeraldi, E. (1999). Clinical and demographic features of psychotic and nonpsychotic depression. Comprehensive Psychiatry, 40(5), 358–362. Klonsky, E. D., May, A. M., & Saffer, B. Y. (2016). Suicide, suicide attempts, and suicidal ideation. Annual Review of Clinical Psychology, 12, 307–330. Auerbach, R. P., Stanton, C. H., Proudfit, G. H., & Pizzagalli, D. A. (2015). Self-referential processing in depressed adolescents: A high-density event-related potential study. Journal of Abnormal Psychology, 124(1), 233–245. Kiang, M., Farzan, F., Blumberger, D. M., Kutas, M., McKinnon, M. C., Kansal, V., et al. (2017). Abnormal self-schema in semantic memory in major depressive disorder: Evidence from event-related brain potentials. Biological Psychology, 126, 41–47. Li, Y., Li, M., Wei, D., Kong, X., Du, X., Hou, X., et al. (2017). Self-referential processing in unipolar depression: Distinct roles of subregions of the medial prefrontal cortex. Psychiatry Research, 263, 8–14. Smeijers, D., Vrijsen, J. N., van Oostrom, I., Isaac, L., Speckens, A., Becker, E. S., et al. (2017). Implicit and explicit self-esteem in remitted depressed patients. Journal of Behavioral Therapy and Experimental Psychiatry, 54, 301–306. Lemogne, C., le Bastard, G., Mayberg, H., Volle, E., Bergouignan, L., Lehéricy, S., et al. (2009). In search of the depressive self: Extended medial prefrontal network during self-referential processing in major depression. Social Cognitive and Affective Neuroscience, 4(3), 305–312. Yoshimura, S., Okamoto, Y., Onoda, K., Matsunaga, M., Ueda, K., Suzuki, S., et al. (2010). Rostral anterior cingulate cortex activity mediates the relationship between depressive symptoms and medial prefrontal cortex activity. Journal of Affective Disorders, 122(1–2), 76–85. Maslim, R. (2013). Diagnosis Gangguan Jiwa, Rujukan Ringkas PPDGJ-III dan DSM-V (2nd ed.). Jakarta: PT Nuh Jaya. Bailey, R., & Pico, J. (2022). Defense Mechanisms. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing. Available at: https://www.ncbi.nlm.nih.gov/books/NBK559106/ Inagaki, M., Ohtsuki, T., Yonemoto, N., Kawashima, Y., Saitoh, A., Oikawa, Y., et al. (2013). Validity of the Patient Health Questionnaire (PHQ)-9 and PHQ-2 in general internal medicine primary care at a Japanese rural hospital: A cross-sectional study. General Hospital Psychiatry, 35(6), 592–597. Bolton, J. M., Gunnell, D., & Turecki, G. (2015). Suicide risk assessment and intervention in people with mental illness. BMJ, 351, h4978. Zalsman, G., Hawton, K., Wasserman, D., van Heeringen, K., Arensman, E., Sarchiapone, M., et al. (2016). Suicide prevention strategies revisited: 10-year systematic review. The Lancet Psychiatry, 3(7), 646–659. Antara, J. (2014). Episode depresif berat dengan gejala psikotik: Sebuah laporan kasus. E-Jurnal Medika Udayana, 4(3). Weickert, T. W., & Goldberg, T. E. (2005). First- and second-generation antipsychotic medication and cognitive processing in schizophrenia. Current Psychiatry Reports, 7(4), 304–310. Bennabi, D., Charpeaud, T., Yrondi, A., Genty, J.-B., Destouches, S., Lancrenon, S., et al. (2019). Clinical guidelines for the management of treatment-resistant depression: French recommendations from experts, the French Association for Biological Psychiatry and Neuropsychopharmacology and the Fondation FondaMental. BMC Psychiatry, 19(1), 262. Kaplan, H. I., Sadock, B. J., & Grebb, J. A. (2010). Sinopsis Psikiatri. Jakarta: Binarupa Aksara. Dawn, M., & Scheick, E. (2011). Developing self-aware mindfulness in the nurse-client relationship: An evaluation and developmental study. Journal of Professional Nursing, 27(2), 114–123.